Noongar Dandjoo Series 3 - Johnston, Michelle; Bishop, Russell (National Indigenous Television, 2012)
'Dandjoo' is the Noongar word for 'gathering' and these DVDs have done just that - gathered together stories, music and interviews from the Perth Noongar Community. 'Noongar Dandjoo' is a series of four programs produced by students from Curtin University and hosted by Dennis Simmons. The programs have been made in close collaboration with the Aboriginal Community of Perth, Western Australia.